Risk Factors for Postoperative Morbidity, Suture Insufficiency, Re-Surgery and Mortality in Patients with Gastroduodenal Perforation - Treuheit, Julia; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
(1) Background: The aim of the present study was to identify risk factors associated with postoperative morbidity, suture/anastomotic insufficiency, re-surgery, and mortality in patients undergoing surgery for gastroduodenal perforation. (2) Methods: A retrospective analysis of 273 adult patients who received surgical treatment for gastroduodenal perforation from January 2006 to June 2021 at the University Hospital Erlangen was performed. The patient demographics and preoperative, intraoperative, and postoperative parameters were collected and compared among the different outcome groups (in-hospital morbidity, suture/anastomotic insufficiency, re-surgery, and 90-day mortality). (3) Results: In-hospital morbidity, suture/anastomotic insufficiency, need for re-surgery, and 90-day mortality occurred in 71%, 10%, 26%, and 25% of patients, respectively. The independent risk factors for morbidity were a significantly reduced general condition, a lower preoperative hemoglobin level, and a higher preoperative creatinine level. The independent risk factors for suture/anastomotic insufficiency could be identified as an intake of preoperative steroids and a perforation localization in the proximal stomach or duodenum. The four parameters were independent risk factors for the need for re-surgery: a significantly reduced general condition, a perforation localization in the proximal stomach, a higher preoperative creatinine level, and a higher preoperative CRP level. An age over 66 years and a higher preoperative CRP level were independent risk factors for 90-day mortality. (4) Conclusions: Our study could identify relevant risk factors for the postoperative outcome of patients undergoing surgical treatment for gastroduodenal perforation. Patients exhibiting the identified risk factors should receive heightened attention in the postoperative period and may potentially benefit from personalized and tailored therapy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: gastroduodenal perforation; morbidity; mortality; re-surgery; risk factors; surgery; suture insufficiency